Characterization of the Vaccine Abdala - Katia Pino Marrero; Alvaro Laurencio Pérez; Dania Vargas Batista (Journal of Current Viruses and Treatment Methodologies, 2021)
Vaccines symbolize the main pandemic control tool in the world, which is why they are the object of study in many investigations. In this work, the Abdala vaccine was characterized in terms of adverse reactions by conducting a survey and statistical processing of the data taken through distribution graphs of the same, developed in the Minitab software 16. Of the people involved, 47.67% presented Symptoms that were mild to moderate with the presence of pain in the area of the injection, drowsiness and decay, mainly. Based on the distribution of the data in histograms, the duration of these symptoms was approximately 1 day. Likewise, it was observed that the symptoms occur mainly in females, for 33.72% of the cases in the first dose and 23.26% after the second dose was applied.
Keywords: Adverse reactions